Healthcare resources are inadequate to address the burden of illness among HIV-infected male prisoners in Malaysia. Issue 4 (19th December 2016) - Bick, Joseph; Culbert, Gabriel; Al-Darraji, Haider A.; Koh, Clayton; Pillai, Veena; Kamarulzaman, Adeeba; Altice, Frederick
Abstract : Purpose: Criminalization of drug use in Malaysia has concentrated people who inject drugs (PWID) and people living with HIV into prisons where health services are minimal and HIV-related mortality is high. Few studies have comprehensively assessed the complex health needs of this population. The paper aims to discuss these issues. Design/methodology/approach: From October 2012 through March 2013, 221 sequentially selected HIV-infected male prisoners underwent a comprehensive health assessment that included a structured history, physical examination, and clinically indicated diagnostic studies. Findings: Participants were mostly PWID (83.7 percent) and diagnosed with HIV while incarcerated (66.9 percent). Prevalence of hepatitis C virus (90.4 percent), untreated syphilis (8.1 percent), active (13.1 percent), and latent (81.2 percent) tuberculosis infection was several fold higher than non-prisoner Malaysian adults, as was tobacco use (71.9 percent) and heavy drinking (30.8 percent). Most (89.5 percent) were aware of their HIV status before the current incarceration, yet few had been engaged previously in HIV care, including pre-incarceration CD4 monitoring (24.7 percent) or prescribed antiretroviral therapy (ART) (16.7 percent). Despite most (73.7 percent) meeting Malaysia's criteria for ART (CD4 <350 cells/ μ L), less than half (48.4 percent) ultimately received it. Nearly one-quarter (22.8 percent) of those with AIDS (<200 cells/ μ L) did not receive ART. Originality/value: Drug addiction and communicable disease comorbidity, which interact negatively and synergistically with HIV and pose serious public health threats, are highly prevalent in HIV-infected prisoners. Interventions to address the critical shortage of healthcare providers and large gaps in treatment for HIV and other co-morbid conditions are urgently needed to meet the health needs of HIV-infected Malaysian prisoners, most of whom will soon transition to the community.